Feasibility and Preliminary Effects of a Multimodal Non-Hormonal Intervention for Women With Early Menopause: A Mixed-Methods Study - Ratih Kumala Dewi; Luluk Khusnul Dwihestie; Benedicta Audrey Putri Trisnadewi; Ratih Paramastuti; Emilia Boavida De Araujo (An Idea Health Journal, 2026)
Background: Early menopause is characterized by hormonal decline, sleep disturbances, psychological distress, and diminished quality of life. Aim this study is developed and evaluated the feasibility and preliminary outcomes of an integrated intervention comprising phytoestrogen-based nutrition, Damask rose aromatherapy, and self-efficacy–based psychological support for women experiencing early menopause. Methods: An exploratory sequential mixed-methods design was implemented in Boyolali Regency, Central Java, Indonesia, from July to September 2025. The research process included needs assessment, intervention development, expert validation, pilot testing, and qualitative evaluation. Thirty-two women with early menopause participated in a four- week, one-group pretest–posttest intervention. Quantitative data were analyzed using paired t-tests or Wilcoxon signed-rank tests, and qualitative data were examined through inductive thematic analysis. The intervention was associated with improvements in several physiological and psychological outcomes. Result: Estradiol levels increased significantly (p = 0.021), HDL levels improved (p = 0.046), and fasting blood glucose decreased (p = 0.012). Significant improvements were also observed in sleep quality (p = 0.002), psychological distress (p < 0.05), menopause-related quality of life (p = 0.019), and menopause self-efficacy (p = 0.001). Conclusion: Qualitative findings demonstrated high acceptability of the intervention and identified perceived benefits, including relaxation, improved sleep, emotional adaptation, and increased confidence in managing menopausal symptoms. These pilot results indicate that an integrated intervention combining phytoestrogen-based nutrition, Damask rose aromatherapy, and self-efficacy–based psychological support is feasible and associated with improvements in hormonal, metabolic, sleep-related, and psychological outcomes among women with early menopause.